New Urbanism and Urban Design Dimension Implementation in Public Space in the Simpang Lima Area, Semarang City - Dini Silvia Anggraini; Wijayanti (Journal of Architecture & Environment, 2023)
New urbanism, originally meant a reform movement and then developed into a new paradigm in urban design. However, recently researchers argue that the attractiveness of new urbanism has begun to diminish so that it has lost its significance. The research was conducted to determine the strengths and weaknesses of the Simpang Lima Area and Jalan Pahlawan Semarang when viewed using the theory of Urban dimension and New Urbanism, so that it can be an evaluation for related parties. The steps taken in the study used three stages, namely the initial stage of description. At this time, the researcher describes what he saw, heard, and understood. For the first time, researchers get a glimpse of the results of the informants. reduction stage. In this stage, researchers retrieve all the information from previous meetings to concentrate on one particular problem. Selection stage. At this stage, the researcher will detail the problem that is the focus, which will then be analyzed in more depth. The research location is at Simpang Lima or called the Pancasila Field which is one of the Landmarks of Semarang City, in the form of an open space used by Semarang City residents for activities. The city of Semarang is synonymous with Simpang Lima because many big events are held here, besides that Simpang Lima is also the center of the crowd of the city of Semarang. The final results of the research produce topics using information that is used to produce some new knowledge, hypotheses, or even theories.